Effects of Input Voltage on Flow Separation Control for Low-Pressure Turbine at Low Reynolds Number by Plasma Actuators. (13th December 2012) - Matsunuma, Takayuki; Segawa, Takehiko
Abstract : Active flow control using dielectric barrier discharge (DBD) plasma actuators was investigated to reattach the simulated boundary layer separation on the suction surface of a turbine blade at low Reynolds number, Re = 1.7 × 10 4 . The flow separation is induced on a curved plate installed in the test section of a low-speed wind tunnel. Particle image velocimetry (PIV) was used to obtain instantaneous and time-averaged two-dimensional velocity measurements. The amplitude of input voltage for the plasma actuator was varied from ±2.0 kV to ±2.8 kV. The separated flow reattached on the curved wall when the input voltage was ±2.4 kV and above. The displacement thickness of the boundary layer near the trailing edge decreased by 20% at ±2.0 kV. The displacement thickness was suddenly reduced as much as 56% at ±2.2 kV, and it was reduced gradually from ±2.4 kV to ±2.8 kV (77% reduction). The total pressure loss coefficient, estimated from the boundary layer displacement thickness and momentum thickness, was 0.172 at the baseline (actuator off) condition. The total pressure loss was reduced to 0.107 (38% reduction) at ±2.2 kV and 0.078 (55% reduction) at ±2.8 kV.